2006
DOI: 10.1016/j.ejcts.2006.02.040
|View full text |Cite
|
Sign up to set email alerts
|

P38 mitogen-activated protein kinase inhibition attenuates pulmonary inflammatory response in a rat cardiopulmonary bypass model

Abstract: These findings suggested that (1) p38 MAP kinase activation is one of the important aspects of the signaling event that mediate the release of TNF-alpha and IL-1beta and contributes to CPB-induced pulmonary inflammatory response, (2) SB203580 selectively inhibiting p38 MAP kinase activation efficaciously reduces pulmonary inflammatory response after CPB, and (3) p38 MAP kinase influence the activation of NF-kappaB in the lung during and after CPB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Furthermore, in reperfused rat lungs, the phosphorylation of p38 MAPK and ERK was also upregulated (13). Our previous study demonstrated that p38 MAPK was activated in rat lungs following CPB and that the inhibitor of p38 MAPK restrained CPB-triggered inflammation (14). Therefore, MAPK signaling serves an important role in acute lung injury and the associated inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in reperfused rat lungs, the phosphorylation of p38 MAPK and ERK was also upregulated (13). Our previous study demonstrated that p38 MAPK was activated in rat lungs following CPB and that the inhibitor of p38 MAPK restrained CPB-triggered inflammation (14). Therefore, MAPK signaling serves an important role in acute lung injury and the associated inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that MAPK signaling was activated in the rat lung tissue following CPB (13). However, this signaling was blocked following MAPK signaling inhibitor treatment, and simultaneously, the release of inflammatory factors and infiltration were restrained (14). Therefore, MAPK signaling may participate in CPB-induced lung injury, although whether NAMPT regulates CPB-triggered inflammation and cellular permeability enhancement of lung tissue through MAPK signaling remains unknown.…”
Section: Introductionmentioning
confidence: 92%
“…The transcription of proinflammatory genes associated with these signaling pathways is dependent on the activation of SAPKs and NF-B (16,28). Chemical inhibitors such as SB-203580 have been frequently used to study the requirement for activation of p38 MAPK in many inflammatory models, including lung inflammation following cardiopulmonary bypass (14), cystic fibrosis (55), and ovalbumin-induced allergy in the airway (18). The role of NF-B in airway inflammation was confirmed by the demonstration that the adenoviral vector-mediated overexpression of IKK in airway epithelial cells of mice was sufficient for NF-B activation, production of inflammatory mediators, and recruitment of neutrophils to the lungs (58).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our findings may also be relevant to other forms of systemic inflammatory activation such as burns [49], ischemia-reperfusion [50] and cardiopulmonary bypass [51,52], where p38MAPK activation and its relation to multi-organ dysfunction is becoming increasingly clear. Inhibitors of the p38MAPK pathway are being investigated in animal and human studies of sepsis and other pro-15 inflammatory disease states [52][53][54][55][56]. Modulation of up-or downstream regulators of this pathway could also be of interest therapeutically.…”
mentioning
confidence: 96%